Preliminary stage development of portable steel chamfering machine / Sia Chee Kiong, Ker Eng Ling and Phang Chang - Sia, Chee Kiong; Ker, Eng Ling; Phang, Chang (2006)
After a part has been machined, a finishing operation is usually required to remove excess material or burrs to bring the part within tolerance of the specification. The finishing operation is a critical step in the manufacturing of parts made with hard metals. The primary finishing processes are deburring and chamfering. In the past and still presently, the finishing step has been performed manually at a burr bench with a hand held spindle grinder. As expected, there are problems with the manual finishing of parts. Manual finishing is inconsistent and inaccurate. If a part is damaged beyond repair, thousands of dollars spent on the initial machining processes can be lost. Manual finishing is also time-consuming (Engel et. al 1992). The development is include the study of the process and the problem occur and the suggestion improvement by design of the new system (portable). The development also considered the material, mechanism and ergonomics. Safety and the efficiency of the process in term of time of the product will be determined at the next stage by using the CAE software and experimental approach.